Man's Relationship with God in The Myth of The Aermata Ratuh Ebuh Tomb in Arosbaya District, Bangkalan District, Madura, East Java - Nurul Hidayah; Resdianto Permata Raharjo (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
This research aims to find out the relationship between humans and God as depicted in the myth of the tomb of Aermata Ratuh Ebuh. The data used in this study are audio/video recordings, images, and notes obtained from direct observation and interviews. This myth has an important role in describing spiritual relationships, connecting the divine dimension with deep social practices. People who believe in this myth consider tombs to be sacred places with divine powers, where individuals can feel God's presence through various rituals and traditions. The discussion includes several aspects: the symbolism of the tomb that marks the presence of God, the rituals and practices that strengthen spiritual relationships, and the moral and ethical values contained in this myth. In addition, the research also explores the challenges faced by this tradition in the modernization era. The findings show that the myth of Aermata Ratuh Ebuh remains relevant as a bridge between humans and God, despite being faced with significant social change. Overall, the relationship between humans and God in the context of the myth of Aermata Ratuh Ebuh remains important and valuable, with the potential to be adapted and maintained despite the changing times. This myth is not just a cultural heritage, but also a spiritual source that enriches human life.